Sacrilegious character of «The cross on Saturn» in the self-titled novel of Oles Ulianenko - Штейнбук, Фелікс Маратович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
Oles Ulianenko, one of the most talented and controversial Ukrainian writers of these days, has been dead for ten years. His literary works did not receive any appropriate professional evaluation though because literary scholars and critics applied either the wrong or unproductive research methodology due to some objective and subjective reasons. The aim of the article is to suggest an alternative, in comparison to traditional variants, theoretical literary analysis which is grounded on the principles of the corporal-mimetic method to interpret fiction done on the extremely controversial novel “The Cross on Saturn” by O. Ulianenko.Having analyzed the idea and artistic content of the novel “The Cross on Saturn”, the conclusion is made that, first, the book characters seem to function as simulacra of their shallowness because they lack the depth of inner world. But despite this fact, despite parody, superficial dialogues and surrogate actions, the main characters of the novel and the peripeteia, they find themselves in, do not lose aesthetic appeal because these characters do not need deep inner world since their function is not determined by what these trivial characters reflect in the text mirror but by what the text mirror reflects in them.Second, the shallowness is filled with the content conditioned by the incest precedent which provides the basis of Oles Ulianenko’s novel to the degree to what the writer creates the tragedy in its exact, namely ancient Geek, meaning of the notion according to which tragedy is, on the one hand, a story determined by an utterly artificial form and content and, on the other hand, it is a story which does not simply end by death, it is a story which cannot end by anything else but death. It seems as if nothing but tragedy could make it impossible for a man to have their animal essence to supersede their human part.